2020
DOI: 10.1002/berj.3695
|View full text |Cite
|
Sign up to set email alerts
|

Education, merit and mobility: Opportunities and aspirations of refugee youth in Kenya’s Kakuma refugee camp

Abstract: Drawing on observations and interviews with teachers and students enrolled in a camp secondary school, this article documents how youth aspirations are constructed, supported and constrained in the context of a limited opportunity structure. Data demonstrate that schools enforce cultural scripts of meritocracy, along with assurances that hard work in school will be rewarded with post‐secondary education and economic returns. The possibilities for upward social mobility driving this narrative were central to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Madziva and Thondhlana argue that a quality education lies at the intersection of these three environments, and cannot be achieved otherwise. The second underlying assumption to refugee youth’s aspirations is that personal responsibility, effort, and accountability are key to the ability to fulfill them (Bellino 2021; Poole and Riggan 2020). The research reviewed below destabilizes these maxims.…”
Section: Relevant Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Madziva and Thondhlana argue that a quality education lies at the intersection of these three environments, and cannot be achieved otherwise. The second underlying assumption to refugee youth’s aspirations is that personal responsibility, effort, and accountability are key to the ability to fulfill them (Bellino 2021; Poole and Riggan 2020). The research reviewed below destabilizes these maxims.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Refugee education scholars have advocated for refugee youths’ access to quality education as a means of providing them with life‐saving physical, psychosocial, and cognitive protection (Burde et al 2017); integration and belonging (Abu El‐Haj et al 2018; Warriner 2007); as well as economic mobility (Dryden‐Peterson et al 2019). Scholars have also questioned these promises for refugee youth, given the challenges that define the contexts in which they are embedded, such as low‐quality schooling refugee camps (Bellino 2021; Mendenhall et al 2015); segregated education in national schools (Chopra and Adelman 2017; Dryden‐Peterson et al 2019); and limited post‐secondary educational and employment opportunities in developing host countries (Horst 2006; Poole and Riggan 2020). Studies concerned with youth in the global south have demonstrated that while quality schooling might aid students in achieving agency and a sense of empowerment, it does not always aid youth in fulfilling their aspirations, including gainful employment, leadership opportunities, and/or a chance to give back to their communities (Bajaj 2009; Jeffrey 2010).…”
Section: Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing shared aspirations to continue postsecondary schooling also drew attention to glaring access barriers and the unwelcome reality that, at the time, less than 1% of refugees globally had access to tertiary education (UNHCR, 2016b(UNHCR, , 2018. Though this opportunity gap was present throughout their schooling, youth co-researchers had selectively upheld meritocratic scripts, assuring themselves and one another that hard work in school would be rewarded (Bellino, 2021). Once they, too, found themselves having completed secondary schooling but with few opportunities to draw on their educational investments, they began to reflect on their participants' views differently.…”
Section: Closing Information Gaps In Kakuma Refugee Camp Kenya: Bellinomentioning
confidence: 99%
“…Education is often touted as providing a sense of purpose amid the uprootedness of refugee status and life constraints in refugee camps [10,11]. It is championed for playing a vital role in facilitating endurance and transitions for refugees by providing them with the skills they need to increase their social capital and ability to adapt to different and challenging contexts [12][13][14][15].…”
Section: Development Through Education or The Status Quo?mentioning
confidence: 99%